Effect of Methotrexate on Recognition Memory in Adult Female Mice - Elmatoni, Wafa F.; Ahmed, Fatima H.; Ghliwo, Hajer M.; Drah, Mustafa M. (Al-Mukhtar Journal of Sciences, 2022)
Methotrexate MTX is used to treat some types of cancers, skin diseases, and rheumatic diseases. Many studies have suggested that it may lead to memory damage in mice. Accordingly, this study was conducted to investigate the effect of different doses of methotrexate on recognition memory in mice. Twenty-four adult female albino mice (weighing between 30-36 g) were divided equally into four groups and subjected to one of the following treatments: the control group (injected with normal saline), the second group treated with a dose of 20 mg/kg of MTX, the third group treated with a dose of 40 mg/kg of MTX, the fourth group treated with a dose of 80 mg/kg of MTX. All doses were given once intraperitoneally. A memory test was performed half an hour after injection, comprising object training and a new object recognition test. The results of this study showed that the MTX-injected mice had a lower rate of exploration of the novel object compared to the control group, and MTX has a dose-dependent negative effect on cognitive behavior. These findings suggest that methotrexate has a negative effect on the recognition memory of mice.